Development of a Web-based E-Learning System for Accounting Education in Higher Education - Anggi Haerani; Rohaelis Nuraisiah; Tauffik Qurohman (Acman: Accounting and Management Journal, 2025)
Web-based e-learning systems have become a major focus in improving accounting learning in higher education. This research aims to design an effective e-learning system to enrich students' learning experience and support better interaction between students and teachers in the context of accounting education. Key challenges in the implementation of e-learning technology include appropriate integration with academic content needs, as well as optimisation of user experience to improve student participation and learning outcomes. Effective evaluation methods are needed to measure the success of e-learning system implementation, considering various evaluation aspects such as user satisfaction, system efficiency, and learning achievement. The impact of using a web-based e-learning system is also analysed on the interaction between students and teachers, which has the potential to enrich the learning experience in the accounting education environment.